2015
DOI: 10.1136/heartjnl-2014-307380
|View full text |Cite
|
Sign up to set email alerts
|

Do repeated risk factor measurements influence the impact of education on cardiovascular mortality?

Abstract: In this cohort, repeated measurements of risk factors seemed to explain more of the educational gradient in CVD mortality. This suggests that a substantial part of the excess CVD mortality among those with lower education might be explained by conventional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It may be argued that using multiple measurements of the explanatory variables would be better as it allows to account for possible changes over time in inequalities in these variables. Recent studies have shown that the contribution of behavioural factors to socioeconomic inequalities in mortality was (slightly) larger when multiple measurements over time of these factors were included [ 44 46 ]. Using the same GLOBE data, Oude Groeniger and colleagues also found a larger contribution of behavioural factors to educational inequalities in mortality when multiple measurements were used, but a smaller contribution of material factors [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that using multiple measurements of the explanatory variables would be better as it allows to account for possible changes over time in inequalities in these variables. Recent studies have shown that the contribution of behavioural factors to socioeconomic inequalities in mortality was (slightly) larger when multiple measurements over time of these factors were included [ 44 46 ]. Using the same GLOBE data, Oude Groeniger and colleagues also found a larger contribution of behavioural factors to educational inequalities in mortality when multiple measurements were used, but a smaller contribution of material factors [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educational attainment was considered as a confounding factor, associated with both smoking and anthropometric measures [25, 26], and was assessed by self-report according to five levels. For stratified analysis we defined three educational levels: basic (until 10 years), secondary (1–4 years after basic), and tertiary (more than 4 years completed education after basic).…”
Section: Methodsmentioning
confidence: 99%
“…The inferior cardiovascular health observed among indigenous peoples relative to non-indigenous peoples in North America may be due to lower socio-economic status and poorer access to quality health care among the former [ 4 ]. A publication from Norway found that differences in smoking habits, systolic blood pressure, serum cholesterol and body mass index explained 72% and 56% of the absolute and relative educational gradients, respectively, in CVD mortality [ 31 ]. Assuming that the educational gradient in Sami and non-Sami populations is the same, the most plausible explanation for the similar levels of risk factors and risk of AMI or CS observed in our study may be that Sami and non-Sami populations in Norway differ little with regard to education levels ( Tables I and II ).…”
Section: Discussionmentioning
confidence: 99%